Study on Impedance Characteristics of Aircraft Cables - Weilin Li; Wenjie Liu; Xiaobin Zhang; Zhaohui Gao; Meng Xie; Hongxia Wang (International Journal of Aerospace Engineering)
Voltage decrease and power loss in distribution lines of aircraft electric power system are harmful to the normal operation of electrical equipment and may even threaten the safety of aircraft. This study investigates how the gap distance (the distance between aircraft cables and aircraft skin) and voltage frequency (variable frequency power supply will be adopted for next generation aircraft) will affect the impedance of aircraft cables. To be more precise, the forming mechanism of cable resistance and inductance is illustrated in detail and their changing trends with frequency and gap distance are analyzed with the help of electromagnetic theoretical analysis. An aircraft cable simulation model is built with Maxwell 2D and the simulation results are consistent with the conclusions drawn from the theoretical analysis. The changing trends of the four core parameters of interest are analyzed: resistance, inductance, reactance, and impedance. The research results can be used as reference for the applications in Variable Speed Variable Frequency (VSVF) aircraft electric power system.